Home advantage in the Australian football league - Clarke, S. (Journal of Sports Sciences, 2005)
The results of this study on home advantage in Australian rules football demonstrate that individual clubs have different home advantages. Traditional measures of home advantage as applied to whole competitions such as percentage of games won, and alternative measures such as average margin of victory for the home team, are calculated. Problems with these measures are discussed. Individual home advantages for each team are obtained using a linear model fitted to individual match margins; the resultant home advantages are analysed, and variations and possible causes or groupings of home advantage are proposed. It is shown that some models allowing different home advantages for different clubs are a significant improvement over previous models assuming a common home advantage. The results show a strong isolation effect, with non-Victorian teams having large home advantages, and lend support to the conclusion that crowd effects and ground familiarity are a major determinant of home advantage.